Study on post partum intrauterine contraceptive device practices and causes for discontinuation of PPIUCD at follow up in a tertiary hospital - Chethan, Radhika; G. S., Anitha; C., Savitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Post partum contraception is the best evidence based intervention in prevention of pregnancy and abortion related maternal morbidity and mortality in the developing countries. The unmet need for contraception among women in the postpartum period can be effectively fulfilled by post partum insertion of IUCD, in a single visit under the Government scheme of providing free maternity services during institutional delivery. Despite optimal efforts by family planning program, very few couples are opting for spacing methods and lack of awareness has resulted in discontinuation of family planning methods particularly PPIUCD. This study is designed to study the practices of PPIUCD and causes for discontinuation at follow up in our hospital. The objectives of the study were study PPIUCD practices at Vanivilas hospital; causes for discontinuation of PPIUCD. Methods: Prospective study done at Vanivilas hospital attached to Bangalore Medical College and Research Institute from January 2014 to December 2014. Women admitted and delivered at VVH, were counselled. CuT 380A was inserted in accepters who fulfilled the Medical Eligibility Criteria and had no contraindications for PPIUCD. They were followed up till June 2016. Results: There were 2072 PPIUCD insertions in one year, out of which 1244 were post placental, 139 were in immediate postpartum and 689 were intra caesarean insertions. Fifty four (54) women discontinued PPIUCD during follow up .Main causes for removal were menstrual abnormalities (19), pain abdomen (13), wanting sterilisation procedure (12) and marital disharmony. Conclusions: PPIUCD is an effective, safe, reversible method of long term contraception with high reported expulsion and low perforation rate, compared to interval insertion. More research is needed in the field of PPIUCD to enhance awareness and acceptance in the community. Awareness and counselling the eligible couples during ante natal care can improve acceptance and compliance of PPIUCD continuation rates.